Interim and Archival Preservation of Plant Specimens in Alcohols for DNA Studies - Lori Elmore Flournoy; Robert Phillip Adam; Ram Naresh Pandy (BioTechniques)
Three plant species, spinach, juniper and broccoli, were stored in different alcohol solutions, and the DNAs were examined to determine changes in the quality and quantity of DNA over time. The smallest changes in the genomic DNA were found in the samples stored in the lower rnol wt alcohols (100% methanol and 100% and 95% ethanol) and when proteinase (Pronase E) was used in the extraction procedure. After 11 months of storage in ethanol, excellent yields of high rnol wt DNA were obtained, but only when the procedure utilized Pronase E. The use of proteinase was found to be essential to obtain DNA from preserved specimens of spinach and broccoli. This appears to explain the previous reports of failures to obtain DNA from alcohol-preserved specimens. Vacuum infiltration of ethanol resulted in better DNA preservation than passive infiltration of ethanol.